Proses Pemesinan Pada Produksi Mesin Pencacah Sabut Kelapa Sawit di PT. Raja Ampat Indotim - Oga Rahadin; Kardiman; Ujiburrahman (Jurnal Serambi Engineering, 2025)
This internship report aims to examine the machining processes involved in the production of an oil palm fiber shredder machine at PT. Raja Ampat Indotim. The background of this study stems from the issue of oil palm fiber waste, which remains underutilized despite its economic potential. The internship focused on observing the step-by-step production process, including the use of milling, turning, bending, drilling, grinding, welding, and finishing operations. The study employed a qualitative approach through direct observation, interviews with machine operators, and documentation of production stages. The results indicate that the machine was successfully assembled over a span of 14 working days, with a shredding capacity of 300–500 kg/hour powered by an 80 HP diesel engine. This study provides insights into the integration of manufacturing techniques within the agricultural machinery industry and highlights the importance of efficient production in supporting sustainable management of agricultural waste.